Perspektif Tenaga Pengajar Program Integrasi Pendidikan Khas Terhadap Infrastruktur di Sekolah - Mohd Yasin, Mohd Hanafi; Mohd Salleh, Noraini; Toran, Hasnah; Tahar, Mohd Mokhtar; Ibrahim, Siti Nur Nadirah (Sains Humanika, 2011)
Teachers and administrators need to constantly monitor and care for students with special needs in line with the trust that must be undertaken. Various aspects should be emphasized to create an environment of effective teaching and learning for students with special needs covering management, safety, facilities and location of the special education program. Infrastructure has a major role in creating a conducive learning environment. Space and classroom environment that is comfortable can increase the effectiveness of learning. Integrated special education programs should have appropriate learning space. Integrated programs should also be equipped with facilities such as toilets for the disabled, special walkways for students with special needs, teaching aids and many more. In addition, safety in schools should be prioritieed in providing adequate learning environment. Classroom locations for the integrated of special education programs need to be in strategic locations to facilitate students mobility. Classroom and school environment that is comfortable is important to ensure student’s comfort in the learning process. However the infrastructure of the school and classrooms for atspecial education programs in this country are found to be at unsatisfactory levels. Several parties responsible in dealing with this matter showed little interest to provide facilities for students special needs. Therefore, this study aimed to evaluate the infrastructure available in schools from the perspective of administrators and teachers in handling special education programs. The result showed that the respondents had little knowledge on information related to special education programs in their school. It was also found that teaching and learning aids for the students with special needs lacking and accessibility to the facilities provided were inadequate.